Solid electrolyte material and battery using the same
Patent Information
- Application Number
- CN202280034724.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-26
- Filing Date
- 2022-03-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-03-31
AI Technical Summary
[0015]根据本公开,能够提供包含碘的新型固体电解质材料。
Smart Images

Figure CN117413323B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to solid electrolyte materials and batteries using the same. Background Technology
[0002] In Patent Document 1, Li3AlF6 is disclosed as a lithium salt contained in a non-aqueous electrolyte or a polymeric electrolyte.
[0003] In Non-Patent Literature 1 and Non-Patent Literature 2, Li3AlF6 was disclosed as a raw material for solid electrolytes.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 63-239781
[0007] Non-patent literature
[0008] Non-patent literature 1: ECS Electrochemistry Letters, 1(6)A87-A89(2012)
[0009] Non-patent literature 2: ACS Appl. Energy Mater., 2, 7196-7203 (2019) Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] The purpose of this disclosure is to provide novel solid electrolyte materials containing iodine.
[0012] Methods for solving problems
[0013] The solid electrolyte material disclosed herein contains Li, M, I and X, where M is at least one element selected from Al, Ga and In, and X is at least one element selected from F, O and S.
[0014] Invention Effects
[0015] According to this disclosure, it is possible to provide novel solid electrolyte materials containing iodine. Attached Figure Description
[0016] Figure 1 This is a cross-sectional view of the battery 1000 according to the second embodiment.
[0017] Figure 2 This is a schematic diagram of a pressure forming die 300 used to evaluate the ionic conductivity of solid electrolyte materials.
[0018] Figure 3This is a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material of Example 1.
[0019] Figure 4 This is a graph showing the initial discharge characteristics of the battery in Example 1. Detailed Implementation
[0020] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings.
[0021] (First Embodiment)
[0022] The solid electrolyte material of the first embodiment comprises Li, M, I, and X. M is at least one element selected from Al, Ga, and In. X is at least one element selected from F, O, and S.
[0023] Solid electrolyte materials are suitable for improving lithium-ion conductivity. The solid electrolyte material of the first embodiment, for example, has high lithium-ion conductivity. Therefore, solid electrolyte materials can be used to obtain batteries with excellent charge-discharge characteristics. An example of such a battery is an all-solid-state secondary battery.
[0024] Here, an example of high lithium-ion conductivity is, for example, 2.8 × 10⁻⁶ near room temperature. -5 S / cm or higher. Room temperature, for example, 25°C. Solid electrolyte materials can have, for example, 2.8 × 10⁻⁶ S / cm. -5 Ionic conductivity above S / cm.
[0025] Solid electrolyte materials may also contain elements that are unavoidably mixed in. Examples of such elements are hydrogen, nitrogen, or oxygen. These elements may be present in the raw material powder of the solid electrolyte material or in the atmosphere used to manufacture or store the solid electrolyte material. The amount of such unavoidably mixed elements in a solid electrolyte material is, for example, less than 1 mol%.
[0026] To improve the ionic conductivity of solid electrolyte materials, the solid electrolyte materials can also be substantially composed of Li, M, I, and X. Here, "the solid electrolyte material is substantially composed of Li, M, I, and X" means that the total amount of Li, M, I, and X is in a molar ratio (i.e., mole fraction) relative to the total amount of all elements constituting the solid electrolyte material is 90% or more. As an example, this molar ratio can also be 95% or more.
[0027] To improve the ionic conductivity of solid electrolyte materials, solid electrolyte materials can also be made solely of Li, M, I, and X.
[0028] Solid electrolyte materials can also be materials represented by the following composition formula (1).
[0029] Li 1-a M a I (1-b)(1+2a) X b(1+2a) / c (1)
[0030] Here, 0<a<1 and 0<b<1 are satisfied. c represents the absolute value of the valence of X. The solid electrolyte material represented by composition formula (1) is suitable for improving ionic conductivity.
[0031] To improve the ionic conductivity of the solid electrolyte material, M may include Al. M may also be Al.
[0032] To improve the ionic conductivity of the solid electrolyte material, X may include F. X may also be F.
[0033] To improve the ionic conductivity of the solid electrolyte material, in composition formula (1), 0.35≤a≤0.5 may be satisfied. In composition formula (1), 0.35≤a≤0.4 may also be satisfied.
[0034] The upper limit value and the lower limit value of the value of a can be defined by any combination of numerical values selected from 0.35, 0.4, 0.48 and 0.5.
[0035] To improve the ionic conductivity of the solid electrolyte material, in composition formula (1), 0.05≤b≤0.67 may be satisfied. In composition formula (1), 0.15≤b≤0.5 may be satisfied, and 0.18≤b≤0.5 may also be satisfied.
[0036] The upper limit value and the lower limit value of the value of b can be defined by any combination of numerical values selected from 0.05, 0.1, 0.15, 0.18, 0.2, 0.33, 0.5 and 0.67.
[0037] The solid electrolyte material may be crystalline, or may be amorphous. Here, the term "crystalline" means that peaks are present in the X-ray diffraction pattern. The term "amorphous" means that broad peaks (i.e., halos) are present in the X-ray diffraction pattern. In the case where amorphous and crystalline phases coexist, peaks and halos are present in the X-ray diffraction pattern.
[0038] The shape of the solid electrolyte material is not limited. Examples of the shape are acicular, spherical, or ellipsoidal. The solid electrolyte material may be in the form of particles. The solid electrolyte material may also have a granular or platy shape.
[0039] When the solid electrolyte material is in the form of particles (e.g., spheres), it can have a median particle size of 0.1 μm or more and 100 μm or less, or a median particle size of 0.5 μm or more and 10 μm or less. This allows for good dispersion of the solid electrolyte material and other materials. The median particle size refers to the particle size (d50) in the volumetric particle size distribution where the cumulative packing is equal to 50%. The volumetric particle size distribution can be determined, for example, by a laser diffraction apparatus or an image analysis apparatus.
[0040] <Manufacturing Methods of Solid Electrolyte Materials>
[0041] Solid electrolyte materials are manufactured, for example, by the methods described below.
[0042] For example, iodide and fluoride raw material powders can be mixed to achieve a target composition.
[0043] As an example, in a target composition of Li 0.5 Al 0.5 I 1.8 F 0.2 In this case, LiI raw material powder, AlI3 raw material powder, and AlF3 raw material powder (i.e., iodide and fluoride raw material powders) are mixed in a molar ratio of approximately LiI:AlI3:AlF3 = 1:0.87:0.13. To offset compositional changes that may occur during the synthesis process, the raw material powders can also be mixed in a pre-adjusted molar ratio.
[0044] If LiI is added, the value of a in equation (1) decreases. If AlF3 is added, the value of b increases.
[0045] Li metal, Al metal, I2 and LiF3 can also be used as raw materials.
[0046] The mixture of raw material powders is mechanically and chemically reacted with each other in a mixing device such as a planetary ball mill to obtain reactants. That is, the raw material powders are reacted with each other using a mechanochemical grinding method. The reactants can also be calcined in a vacuum or an inert atmosphere. Alternatively, the mixture of raw material powders can be calcined in a vacuum or an inert atmosphere to obtain reactants. Examples of inert atmospheres include helium, argon, and nitrogen.
[0047] Solid electrolyte materials are obtained through the methods described above.
[0048] (Second Implementation)
[0049] The second embodiment will be described below. Matters described in the first embodiment will be omitted as appropriate.
[0050] The battery of the second embodiment includes a positive electrode, an electrolyte layer, and a negative electrode. The electrolyte layer is disposed between the positive electrode and the negative electrode. At least one of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material of the first embodiment.
[0051] The battery of the second embodiment has excellent charge and discharge characteristics because it contains the solid electrolyte material of the first embodiment.
[0052] Figure 1 This is a cross-sectional view of the battery 1000 according to the second embodiment.
[0053] The battery 1000 has a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203.
[0054] The positive electrode 201 contains positive electrode active material 204 and solid electrolyte 100.
[0055] The negative electrode 203 contains negative electrode active material 205 and solid electrolyte 100.
[0056] Solid electrolyte 100 comprises particles containing the solid electrolyte material of the first embodiment. Solid electrolyte 100 may also be particles containing the solid electrolyte material of the first embodiment as a main component. Particles containing the solid electrolyte material of the first embodiment as a main component refer to particles in which the solid electrolyte material of the first embodiment is contained at most in a molar ratio. Solid electrolyte 100 may also be particles made from the solid electrolyte material of the first embodiment.
[0057] The positive electrode 201 contains a material capable of inserting and deintercalating metal ions such as lithium ions. This material is, for example, positive electrode active material 204.
[0058] Examples of positive electrode active material 204 include lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal sulfides, or transition metal nitrides. Examples of lithium-containing transition metal oxides include Li(Ni, Co, Mn)O2, Li(Ni, Co, Al)O2, or LiCoO2.
[0059] In this disclosure, “(A, B, C)” means “at least one selected from A, B and C”.
[0060] The shape of the positive electrode active material 204 is not limited to a specific shape. The positive electrode active material 204 can also be particles. The positive electrode active material 204 can also have a median particle size of 0.1 μm or more and 100 μm or less. When the positive electrode active material 204 has a median particle size of 0.1 μm or more, the positive electrode active material 204 and the solid electrolyte 100 can be well dispersed in the positive electrode 201. This improves the charge-discharge characteristics of the battery 1000. When the positive electrode active material 204 has a median particle size of 100 μm or less, the lithium diffusion rate within the positive electrode active material 204 is increased. This allows the battery 1000 to operate at high output power.
[0061] The positive electrode active material 204 can also have a larger median particle size than the solid electrolyte 100. Therefore, the positive electrode active material 204 and the solid electrolyte 100 can be well dispersed in the positive electrode 201.
[0062] In order to improve the energy density and output power of the battery 1000, in the positive electrode 201, the ratio of the volume of the positive electrode active material 204 to the total volume of the positive electrode active material 204 and the solid electrolyte 100 can also be 0.30 or more and 0.95 or less.
[0063] To improve the energy density and output power of the battery 1000, the positive electrode 201 can also have a thickness of more than 10 μm and less than 500 μm.
[0064] Electrolyte layer 202 contains an electrolyte material. This electrolyte material is, for example, a solid electrolyte material. Electrolyte layer 202 may also be a solid electrolyte layer. Electrolyte layer 202 may also contain the solid electrolyte material of the first embodiment.
[0065] The electrolyte layer 202 may also contain 50% by mass or more of the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also contain 70% by mass or more of the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also contain 90% by mass or more of the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also be made solely of the solid electrolyte material of the first embodiment.
[0066] Hereinafter, the solid electrolyte material of the first embodiment will be referred to as the first solid electrolyte material. Solid electrolyte materials different from the first solid electrolyte material will be referred to as the second solid electrolyte material.
[0067] The electrolyte layer 202 may contain not only a first solid electrolyte material but also a second solid electrolyte material. The first and second solid electrolyte materials may be uniformly dispersed within the electrolyte layer 202. The layers formed from the first and second solid electrolyte materials may also be stacked along the stacking direction of the battery 1000.
[0068] The electrolyte layer 202 may also be made of only the second solid electrolyte material.
[0069] The electrolyte layer 202 can also have a thickness of 1 μm or more but less than 1000 μm. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 become less prone to short circuits. When the electrolyte layer 202 has a thickness of less than 1000 μm, the battery 1000 can operate at high output power.
[0070] The negative electrode 203 contains a material capable of inserting and deintercalating metal ions such as lithium ions. This material is, for example, the negative electrode active material 205.
[0071] Examples of negative electrode active materials 205 include metallic materials, carbon materials, oxides, nitrides, tin compounds, or silicon compounds. Metallic materials can be elemental metals or alloys. Examples of metallic materials include lithium metal or lithium alloys. Examples of carbon materials include natural graphite, coke, graphitized carbon, carbon fibers, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds, or tin compounds.
[0072] The shape of the negative electrode active material 205 is not limited to a specific shape. The negative electrode active material 205 can also be particles. The negative electrode active material 205 can also have a median particle size of 0.1 μm or more and 100 μm or less. When the negative electrode active material 205 has a median particle size of 0.1 μm or more, the negative electrode active material 205 and the solid electrolyte 100 can be well dispersed in the negative electrode 203. This improves the charge-discharge characteristics of the battery 1000. When the negative electrode active material 205 has a median particle size of 100 μm or less, the lithium diffusion rate within the negative electrode active material 205 is increased. This allows the battery 1000 to operate at high output power.
[0073] The negative electrode active material 205 can also have a larger median particle size than the solid electrolyte 100. Therefore, the negative electrode active material 205 and the solid electrolyte 100 can be well dispersed in the negative electrode 203.
[0074] In order to improve the energy density and output power of the battery 1000, in the negative electrode 203, the ratio of the volume of the negative electrode active material 205 to the total volume of the negative electrode active material 205 and the solid electrolyte 100 can also be 0.30 or more and 0.95 or less.
[0075] To improve the energy density and output power of the battery 1000, the negative electrode 203 can also have a thickness of more than 10 μm and less than 500 μm.
[0076] For the purpose of improving ionic conductivity, chemical stability and electrochemical stability, at least one of the cathode 201, electrolyte layer 202 and anode 203 may also contain a second solid electrolyte material.
[0077] The second solid electrolyte material can also be a halide solid electrolyte.
[0078] Examples of halide solid electrolytes are Li₂MgX'₄, Li₂FeX'₄, LiAlX'₄, Li(Ga,In)X'₄, or Li₃(Al,Ga,In)X'₆. Here, X' is selected from at least one of F, Cl, Br, and I.
[0079] Other examples of halide solid electrolytes are those made of Li p Me q Y r The compound represented by Z6 satisfies p + m'q + 3r = 6 and r > 0. Me is at least one element selected from metallic and half-metallic elements other than Li and Y. Z is at least one element selected from F, Cl, Br, and I. The value of m' represents the valence of Me. "Half-metallic elements" are B, Si, Ge, As, Sb, and Te. "Metallic elements" are all elements contained in Groups 1 to 12 of the periodic table (except hydrogen) and all elements contained in Groups 13 to 16 of the periodic table (except B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se). From the viewpoint of improving the ionic conductivity of halide solid electrolytes, Me can also be at least one element selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb.
[0080] The second solid electrolyte material can also be a sulfide solid electrolyte.
[0081] Examples of sulfide solid electrolytes include Li₂S-P₂S₅, Li₂S-SiS₂, Li₂S-B₂S₃, Li₂S-GeS₂, and Li₂S-P₂S₅. 3.25 Ge 0.25 P 0.75 S4 or Li 10 GeP2S12 .
[0082] The second solid electrolyte material can also be an oxide solid electrolyte.
[0083] The second solid electrolyte material can also be an oxide solid electrolyte.
[0084] Examples of oxide solid electrolytes are:
[0085] (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or its elemental substitutes; (ii) perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGe4O 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4, or their elemental substitutes; (iv) Li7La3Zr2O 12 Garnet-type solid electrolytes such as or elementally substituted compounds thereof; or (v)Li3PO4 or its N-substituted compounds thereof.
[0086] The second solid electrolyte material can also be an organic polymer solid electrolyte.
[0087] Examples of organic polymer solid electrolytes include compounds of polymers and lithium salts. Polymers can also have an ethylene oxide structure. Polymers with an ethylene oxide structure can contain a large amount of lithium salt, thus further increasing ionic conductivity.
[0088] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. A single lithium salt selected from these can be used. Alternatively, a mixture of two or more lithium salts selected from these can be used.
[0089] For the purpose of facilitating the acceptance and donation of lithium ions and improving the output power characteristics of the battery, at least one of the positive electrode 201, electrolyte layer 202 and negative electrode 203 may also contain a non-aqueous electrolyte, a gel electrolyte or an ionic liquid.
[0090] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0091] Examples of non-aqueous solvents include cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorinated solvents. Examples of cyclic carbonate solvents include ethylene carbonate, propylene carbonate, or butenyl carbonate. Examples of chain carbonate solvents include dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents include tetrahydrofuran, 1,4-dioxane, or 1,3-dioxacyclopentane. Examples of chain ether solvents include 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents include γ-butyrolactone. Examples of chain ester solvents include methyl acetate. Examples of fluorinated solvents include fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethyl carbonate. One non-aqueous solvent selected from these may be used alone. Alternatively, a mixture of two or more non-aqueous solvents selected from these may be used.
[0092] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. A single lithium salt selected from these can be used. Alternatively, a mixture of two or more lithium salts selected from these can be used. The concentration of the lithium salt is, for example, 0.5 mol / L or more and 2 mol / L or less.
[0093] As a gel electrolyte, a polymeric material impregnated with a non-aqueous electrolyte can be used. Examples of polymeric materials include polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or polymers containing ethylene oxide bonds.
[0094] Examples of cations contained in ionic liquids are: (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium; (ii) aliphatic cyclic ammonium such as pyrrolidineonium, morpholinium, imidazolineonium, tetrahydropyrimidineonium, piperazineonium or piperidinium; or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridinium or imidazolineonium.
[0095] An example of anion contained in ionic liquids is PF6. - BF4 - SbF6 - AsF6 - SO3CF3 - N(SO2CF3)2 - N(SO2C2F5)2 - N(SO2CF3)(SO2C4F9) - Or C(SO2CF3)3 - .
[0096] Ionic liquids can also contain lithium salts.
[0097] For the purpose of improving the adhesion between particles, at least one of the positive electrode 201, electrolyte layer 202 and negative electrode 203 may also contain a binder.
[0098] Examples of adhesives include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aromatic polyamide resins, polyamides, polyimides, polyamide-imides, polyacrylonitrile, polyacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene-butadiene rubber, or carboxymethyl cellulose. Copolymers can also be used as adhesives. Examples of such adhesives are copolymers selected from two or more materials chosen from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trichlorofluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. Mixtures of two or more materials selected from the above-mentioned materials can also be used as adhesives.
[0099] For the purpose of improving electronic conductivity, at least one of the positive electrode 201 and the negative electrode 203 may also contain a conductive additive.
[0100] Examples of conductive additives include: (i) graphite-based materials such as natural or artificial graphite; (ii) carbon black-based materials such as acetylene black or Ketjen black; (iii) conductive fibers such as carbon fibers or metal fibers; (iv) fluorinated carbon; (v) metal powders such as aluminum; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) conductive metal oxides such as titanium oxide; or (viii) conductive polymers such as polyaniline, polypyrrole, or polythiophene. For cost reduction, conductive additives of (i) or (ii) above may also be used.
[0101] Examples of the battery shape in the second embodiment include coin type, cylindrical type, square type, sheet type, button type, flat type, or stacked type.
[0102] Example
[0103] The present disclosure will now be described in more detail with reference to the embodiments and comparative examples.
[0104] (Example 1)
[0105] (Preparation of solid electrolyte materials)
[0106] In an argon atmosphere with a dew point below -60°C (hereinafter referred to as "dry argon atmosphere"), LiI, AlI3, and AlF3 were prepared as raw material powders in a molar ratio of LiI:AlI3:AlF3 = 1:0.87:0.13. These raw material powders were pulverized and mixed in a mortar. This process was repeated to obtain a mixed powder. The mixed powder was then ground using a planetary ball mill at 500 rpm for 12 hours. This process was repeated to obtain the powder of the solid electrolyte material of Example 1. The solid electrolyte material of Example 1 has Li... 0.5 Al 0.5 I 1.8 F 0.2 The components of the representation.
[0107] The Li content per unit weight of the solid electrolyte material in Example 1 was determined by atomic absorption spectrometry. The Al and I contents of the solid electrolyte material in Example 1 were determined by high-frequency inductively coupled plasma optical emission spectrometry. Based on the Li, Al, and I contents obtained from these measurements, the Li:Al:I molar ratio was calculated. The result showed that the solid electrolyte material of Example 1, like the raw material powder, had a Li:Al:I molar ratio of 1:1:3.6.
[0108] (Evaluation of ionic conductivity)
[0109] Figure 2 This is a schematic diagram of a pressure forming die 300 used to evaluate the ionic conductivity of solid electrolyte materials.
[0110] The pressure forming die 300 includes an upper punch 301, a die frame 302, and a lower punch 303. Both the upper punch 301 and the lower punch 303 are made of electrically conductive stainless steel. The die frame 302 is made of insulating polycarbonate.
[0111] use Figure 2 The pressure forming die 300 shown is used to measure the ionic conductivity of the solid electrolyte material of Example 1 by the following method.
[0112] In a dry atmosphere with a dew point below -30°C, the powder of the solid electrolyte material of Example 1 (i.e., Figure 2 The powder 101, which is a solid electrolyte material, is filled inside the pressure forming die 300. Inside the pressure forming die 300, a pressure of 300 MPa is applied to the powder 101 of the solid electrolyte material of Example 1 using the upper part 301 and the lower part 303 of the punch.
[0113] Under pressure, the upper part 301 and the lower part 303 of the punch are connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper part 301 of the punch is connected to the working electrode and the terminal for potential measurement. The lower part 303 of the punch is connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte material is measured at room temperature by electrochemical impedance spectroscopy.
[0114] Figure 3 This is a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material in Example 1. Figure 3 In the diagram, the vertical axis represents the imaginary component of the impedance, and the horizontal axis represents the real component of the impedance.
[0115] Figure 3 In this context, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is smallest is considered the resistance of the solid electrolyte material for ion conduction. Regarding this real value, refer to... Figure 3 The arrow R shown se Using this resistance value, the ionic conductivity is calculated based on the following mathematical formula (2).
[0116] σ=(R se ×S / t) -1 (2)
[0117] Here, σ represents the ionic conductivity. S represents the contact area between the solid electrolyte material and the upper part 301 of the punch. S in Figure 2 R represents the cross-sectional area of the hollow portion of the mold frame 302. se This represents the resistance value of the solid electrolyte material used in impedance measurement. t represents the thickness of the solid electrolyte material. t in... Figure 2 The thickness of the layer formed by the powder 101 of the solid electrolyte material is indicated in the figure.
[0118] The ionic conductivity of the solid electrolyte material in Example 1, measured at 22°C, was 3.2 × 10⁻⁶. -5 S / cm.
[0119] (Battery manufacturing)
[0120] In a dry argon atmosphere, the solid electrolyte material of Example 1, Li4Ti5O, was prepared in a weight ratio of 65:30:5. 12 And carbon fiber (VGCF). These materials are mixed in a mortar. This process is repeated to obtain a mixture. It should be noted that "VGCF" is a registered trademark of Showa Denko Co., Ltd.
[0121] In an insulating cylinder with an inner diameter of 9.5 mm, a sulfide solid electrolyte of the silver-germanium sulfide type, namely Li6PS5Cl (80 mg), the solid electrolyte material of Example 1 (20 mg), the above mixture (18 mg), and VGCF (2 mg) are sequentially stacked. A pressure of 740 MPa is applied to the stack to form a solid electrolyte layer and a first electrode.
[0122] Next, an In foil, a Li foil, and another In foil are sequentially stacked on the solid electrolyte layer. A pressure of 40 MPa is applied to the stack to form the second electrode.
[0123] Next, a current collector made of stainless steel is installed on the first and second electrodes, and a current collector lead is installed on the current collector.
[0124] Finally, an insulating ring is used to isolate the inside of the insulating cylinder from the outside atmosphere, thus sealing the inside of the cylinder. This process yields the battery of Example 1.
[0125] (Charge / Discharge Test)
[0126] Figure 4 This is a graph showing the initial discharge characteristics of the battery in Example 1. Figure 4 In the diagram, the vertical axis represents voltage, and the horizontal axis represents capacity. Initial discharge characteristics are determined using the methods described below.
[0127] The battery in Example 1 was placed in a constant temperature bath at 85°C.
[0128] At 67μA / cm 2 The current density was used to charge the battery of Example 1 until it reached a voltage of 0.60V. This current density corresponds to a 0.05C rate.
[0129] Next, at 67 μA / cm 2 The current density was used to discharge the battery of Example 1 until it reached a voltage of 1.05V.
[0130] The results of the charge-discharge test showed that the battery in Example 1 had an initial discharge capacity of 871 μAh.
[0131] (Examples 2-9)
[0132] (Preparation of solid electrolyte materials)
[0133] In Example 2, LiI, AlI3 and AlF3 were prepared as raw material powders in a molar ratio of LiI:AlI3:AlF3 = 1:0.56:0.44.
[0134] In Example 3, LiI, AlI3 and AlF3 were prepared as raw material powders in a molar ratio of LiI:AlI3:AlF3 = 1:0.33:0.67.
[0135] In Example 4, LiI, AlI3 and AlF3 were prepared as raw material powders in a molar ratio of LiI:AlI3:AlF3 = 1:0.11:0.89.
[0136] In Example 5, LiI, Li2O and AlI3 were prepared as raw material powders in a molar ratio of LiI:Li2O:AlI3 = 0.9:0.1:1.
[0137] In Example 6, LiI, Li2O and AlI3 were prepared as raw material powders in a molar ratio of LiI:Li2O:AlI3 = 0.5:0.5:1.
[0138] In Example 7, LiI, Li2O and AlI3 were prepared as raw material powders in a molar ratio of LiI:Li2O:AlI3 = 0.7:0.3:0.7.
[0139] In Example 8, LiI, Li2S and AlI3 were prepared as raw material powders in a molar ratio of LiI:Li2S:AlI3 = 0.9:0.1:1.
[0140] In Example 9, LiI, Li2S and AlI3 were prepared as raw material powders in a molar ratio of LiI:Li2S:AlI3 = 0.5:0.5:1.
[0141] Apart from the matters mentioned above, the same procedures as in Example 1 were followed to obtain the solid electrolyte materials of Examples 2 to 9.
[0142] (Evaluation of ionic conductivity)
[0143] The ionic conductivity of the solid electrolyte materials in Examples 2-9 was measured in the same manner as in Example 1. The results are shown in Table 1.
[0144] (Charge / Discharge Test)
[0145] Using the solid electrolyte materials of Examples 2-9, and operating in the same manner as in Example 1, batteries of Examples 2-9 were obtained. The batteries of Examples 2-9 were charged and discharged as well as the battery of Example 1.
[0146] (Comparative Examples 1-8)
[0147] (Preparation of solid electrolyte materials)
[0148] As solid electrolyte materials for Comparative Examples 1-8, Li3AlF6, LiAlI4, and Li 0.5 Al 0.5 I 1.8 Cl 0.2 Li 0.5 Al 0.5 I 1.34 Cl 0.66 Li 0.5 Al 0.5 ICl, Li 0.5 Al 0.5 I 1.8 Br 0.2 Li 0.5 Al 0.5 I 1.34 Br 0.66 and Li 0.5 Al 0.5 IBr.
[0149] (Evaluation of ionic conductivity)
[0150] The ionic conductivity of the solid electrolyte materials in Comparative Examples 1-8 was measured in the same manner as in Example 1. The results are shown in Table 1.
[0151] [Table 1]
[0152]
[0153] (Inspection)
[0154] As shown in Table 1, the solid electrolyte materials of Examples 1–9 have a temperature of 2.8 × 10⁻⁶ near room temperature. -5 High ionic conductivity above S / cm.
[0155] Ga and In are in the same group as Al. Therefore, the same effect can be expected even when M contains Ga or In.
[0156] It is believed that when the solid electrolyte material is crystalline, there is a correlation between ionic conductivity and the crystal structure of the solid electrolyte material. Conversely, it is believed that when the solid electrolyte material is amorphous, there is a correlation between ionic conductivity and the coordination polyhedral structure of the solid electrolyte material. Here, solid electrolyte materials containing Ga or In can have the same crystal structure and coordination polyhedral structure as solid electrolyte materials containing Al. Therefore, even when M contains Ga or In, an improvement in ionic conductivity can be expected.
[0157] All the batteries in Examples 1 to 9 were charged and discharged at room temperature.
[0158] As described above, the solid electrolyte material disclosed herein is a material that can improve the conductivity of lithium ions and is suitable for providing a battery that can be well charged and discharged.
[0159] Industrial availability
[0160] The solid electrolyte material disclosed herein is used, for example, in batteries such as all-solid-state lithium-ion secondary batteries.
[0161] Explanation of symbols
[0162] 100 Solid Electrolytes
[0163] 101 Powder of solid electrolyte material
[0164] 201 Positive Electrode
[0165] 202 Electrolyte Layer
[0166] 203 Negative electrode
[0167] 204 Positive Electrode Active Material
[0168] 205 Negative Electrode Active Material
[0169] 300 Pressure Forming Die
[0170] 301 Upper part of the punch
[0171] 302 Module
[0172] 303 Lower part of the punch
[0173] 1000 batteries
Claims
1. A solid electrolyte material represented by the following composition formula (1), Li 1-a M a I (1-b)(1+2a) X b(1+2a) / c (1) M is at least one element selected from Al, Ga and In, X is at least one element selected from F, O and S, wherein 0<a<1 and 0<b<1 are satisfied, c represents the absolute value of the valence of X, further, in the composition formula (1), at least one selected from 0.35≤a≤0.48 and 0.05≤b≤0.67 is satisfied.
2. The solid electrolyte material according to claim 1, wherein, M includes Al.
3. The solid electrolyte material according to claim 1, wherein, X includes F.
4. The solid electrolyte material according to claim 1, wherein, In the composition formula (1), 0.35≤a≤0.4 is satisfied.
5. The solid electrolyte material according to claim 1, wherein, In the composition formula (1), 0.15≤b≤0.5 is satisfied.
6. A battery, comprising: a positive electrode; a negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode, in, wherein at least one selected from the positive electrode, the negative electrode and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Lithium ion conductive eiectrolyte
JP1988239781A
Sulfide solid electrolytic material
JP2015076316A
Method for manufacturing electrode complex
JP2020074289A
Solid electrolyte material and battery using same
WO2021002053A1
